2010
DOI: 10.1037/a0016338
|View full text |Cite
|
Sign up to set email alerts
|

Why are narcissists so charming at first sight? Decoding the narcissism–popularity link at zero acquaintance.

Abstract: On the basis of a realistic behavioral approach, the authors showed that narcissists are popular at zero acquaintance and aimed to explain why this is the case. In Study 1, a group of psychology freshmen (N = 73) judged each other on the basis of brief self-introductions using a large round-robin design (2,628 dyads). Three main findings were revealed: First, narcissism leads to popularity at first sight. Second, the aspects of narcissism that are most maladaptive in the long run (exploitativeness/entitlement)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
378
4
8

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(411 citation statements)
references
References 82 publications
21
378
4
8
Order By: Relevance
“…Young and Pinsky (2006), for instance, showed that celebrities were more narcissistic than the general population, and that reality television personalities were the most narcissistic. Back, Schmulke, and Egloff (2010) examined why people are commonly attracted to narcissists. Across three studies, they found that when first meeting, people who are more narcissistic made a more positive impression and were more popular than were those who were less narcissistic.…”
Section: Narcissism Qualities and Dimensionsmentioning
confidence: 99%
“…Young and Pinsky (2006), for instance, showed that celebrities were more narcissistic than the general population, and that reality television personalities were the most narcissistic. Back, Schmulke, and Egloff (2010) examined why people are commonly attracted to narcissists. Across three studies, they found that when first meeting, people who are more narcissistic made a more positive impression and were more popular than were those who were less narcissistic.…”
Section: Narcissism Qualities and Dimensionsmentioning
confidence: 99%
“…Narcissists can be charming at first contact, but they tend to become less popular over time as people get to know them (Back, Schmukle, & Egloff, 2010;Paulhus, 1998). Narcissists may not get the opportunity to lead and dominate others if they alienate peers and superiors who could block them from grabbing power.…”
Section: Do Narcissists Undermine Their Self-enhancement Goals?mentioning
confidence: 99%
“…First, past theorizing on the leadership outcomes of narcissism (Padilla, Hogan, & Kaiser, 2007) has differentiated narcissism's association with leadership emergence (i.e., "whether (or to what degree) an individual is viewed as a leader by others, who typically have only limited information about that individual's performance"; Judge, Bono, Ilies, & Gerhardt, 2002, p. 767; Lord, de Vader, & Alliger, 1986) versus narcissism's association with leadership effectiveness (i.e., "a leader's performance in influencing and guiding the activities of his or her unit toward achievement of its goals" [Judge et al, 2002, p. 767; see Stogdill, 1950]). Research shows that narcissists generally make a positive first impression, as others preliminarily perceive them to be charming and self-confident; but over time more negative qualities such as arrogance, exploitativeness, and self-centeredness damage narcissists' relationships (Back, Schmukle, & Egloff, 2010;Paulhus, 1998;Robins & Beer, 2001). Second, past inconsistent findings might be attributable to the use of different sources of leadership reports, with self-reports of leadership outcomes likely yielding larger correlations to 4 G r i j a lva , H a r m s , N e w m a N , G a d d i s & F r a l e y i N P e r s o n n e l P s y c h o l o g y 6 8 ( 2 0 1 5 ) narcissism because narcissists tend to inflate their own importance and achievements.…”
mentioning
confidence: 99%
“…RAM proposes that for others to accurately judge a personality trait, it must have relevant, observable behavioral manifestations that others are able to correctly interpret (Funder, 1995). For narcissism, the behavioral manifestations that contribute to positive first impressions include the tendency to be well-dressed, use charming facial expressions, display self-assured body movements, and use verbal humor (Back et al, 2010;Vazire, Naumann, Rentfrow, & Gosling, 2008). These traits are relevant because they "are related to four generally valued aspects of targets: attractiveness, competence, interpersonal warmth, and humor" (Back et al, 2010, p. 134; see also Berscheid & Reis, 1998).…”
mentioning
confidence: 99%